PENERAPAN URBAN FARMING DENGAN SISTEM FERTIGASI PADA KUBIS BUNGA UNTUK MASYARAKAT MANDIRI PANGAN - Hazen Arrazie Kurniawan; Nurhajijah Nurhajijah; Wiidani Lubis; Imam Hartono Bangun (Universitas Mataram, 2022)
Urban farming is one solution in solving food problems in Indonesia by utilizing vacant land so that people can improve the household economy. An example of a problem case is that of rice farmers in Pematang Ganjang Village, this is an important problem for farmer groups in Pematang Ganjang Village because they only depend on one livelihood, namely rice cultivation. Meanwhile, in Pematang Ganjang village, income is still seasonal, the majority in the village only grows rice. So, when the new planting season there are jobs for farmers. The purpose of this activity is to create a food self-sufficient community in order to create welfare for farmers in Pematang Ganjang Village by cultivating cabbage flowers in empty yards. The benefits to be achieved in this activity include increasing skills and knowledge in the use of vacant land and house yards with a fertigation system in Pematang Ganjang Village. The achievement of government programs related to urban farming as a form of achieving food independence for the community. With the knowledge gained in this activity, farmers do not need to rely on one source of income, but farmers get additional income from cabbage flower cultivation. To create a food self-sufficient community in order to create welfare for farmers in Pematang Ganjang Village. Based on the problems that occur in the field, the solution to this problem is the Participatory Rural Appraisal approach, the lecture method, demonstration plots and mentoring. PKM training implementation procedures. The results of the service activities that have been carried out show that farmers are enthusiastic about transferring technology to the fertigation system and implementing urban farming by utilizing their yards as an additional livelihood for farmers who initially only had one livelihood.